JURIDICAL ANALYSIS OF THE NAME TRANSFER PROCESS OF LAND RIGHTS AS MARITAL COMMUNITY PROPERTY (A Case Study at the Office of Notary & Land Deed Official YONDRI DARTO, S.H. in Batam) - Nadia Defani; Laily Washliati; Agus Siswanto Siagian (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The process of transferring land rights as part of marital property after divorce is an important aspect in providing legal certainty for the entitled parties. Within the national legal framework, joint property is explicitly regulated in Article 35 paragraph (1) of the UUP, and to implement the transfer of rights, an authentic deed in the form of a Deed of Separation and Division of Joint Property is required, drawn up by a notary in accordance with the authority based on Article 15 paragraph (1) of the Notary Law. This deed then becomes the basis for the PPAT to issue an APHB for the purpose of transferring ownership at the Land Office. This study aims to analyze the process of transferring land rights to joint property through a research study at the Notary and PPAT Yondri Darto, S.H., in Batam. This study analyzes the legal regulations, their implementation, as well as the obstacles and solutions. This study uses a descriptive method with a normative approach (legal research) to obtain secondary data and an empirical approach (sociological jurisprudence) to obtain primary data through field research. Based on the results of the study, it can be concluded that the mechanism of transfer of ownership through the Deed of Separation and Division of Joint Property and APHB is a legal and efficient solution, as long as the procedures and documents are fulfilled in accordance with legal provisions. Obstacles that often arise include a lack of understanding by the parties and administrative obstacles. Therefore, the parties are advised to immediately take legal steps after divorce, while Notaries and PPATs ensure procedural compliance with the support of legal education, administration, and technology-based service systems.